(untitled) (Journal of history, 2021)
The article examines the activities of the Kazakh Institute of Public Education according to the docu ments of the Kyzylorda State Regional Archives Foundation of the Republic of Kazakhstan. The questions considered at the meetings of the Presidium, the school council of the institute of public education, the council of student activists of KINO are presented. The regulation on the Kazakh Institute of Public Edu cation and job descriptions of employees, teaching staff, training and production plans, programs and work plans of the studied disciplines, programs on the methodology of teaching disciplines and their content are disclosed. The content of curricula on the methodology of the native language, drawing, geography, social science, theory and practice of the labor school, which were prepared by A. Bayturu sunov, T. Shonanuly, Burabayev, is revealed. On the basis of archival sources, the number of students, the disciplines they studied, industrial practices, methods of lecturing and conducting laboratory classes are stated. The abilities that form students as a result of studying subjects (especially the competence of joint work in a team) are analyzed based on archival documents. The internal discipline of the institute, the formation and work of subject examination commissions to assessment the knowledge of students, shortcomings and gaps, difficulties in the educational process are characterized. The scholarship of stu dents and its size, as well as the living conditions of students are considered. Key words: Kazakh ASSR, Kazakh Institute of Public Education, Kyzylorda State Regional Archives, teacher, student, educational and production plans, curricula, practice, lesson.